Variscan thermal overprints exemplified by U-Th-Pb monazite and K-Ar muscovite and biotite dating at the eastern margin of the Bohemian Massif (East Sudetes, Czech Republic) - Schulmann,K.; Oliot,E.; Kosulicova,M.; Montigny,R.; Stipska,P. (Journal of Geosciences, 2014)
Potassium-argon method on muscovite and biotite and chemical U-Th-Pb method on monazite have been used to date various tectonic and thermal processes affecting the Silesian orogenic wedge at the eastern Variscan front (NE Bohemian Massif). This wedge is composed of three structural units showing an increasing Barrovian metamorphic gradient from the east to the west and LP-HT reworking related to voluminous granite intrusion of the Zulova Pluton in the central part. Three groups of ages are reported: 1) Mississippian (340-320 Ma) K-Ar muscovite ages from the western kyanite zone and easternmost biotite-chlorite zone, ˜320 Ma U-Th-Pb ages of monazite inclusions in syn-burial S1fabric preserved in garnets of the kyanite zone, 2) Pennsylvanian-Early Permian (˜310-290 Ma) K-Ar ages on muscovite and biotite and matrix monazite from the sillimanite and staurolite zones of the central part of the wedge, 3) Early to Mid-Permian K-Ar muscovite and biotite and U-Th-Pb matrix monazite ages (˜280-260 Ma) from the southern part of the area, adjacent to the Sudetic fault system. The sequence of obtained ages is interpreted as reflecting the Mississippian formation of the Silesian orogenic wedge that was followed by crustal-scale detachment related to Pennsylvanian-Early Permian intrusion of a voluminous Zulova Pluton accompanied by important fluid flow. Finally, the southern part of the studied domain was probably reworked by Permian fault system associated with renewed fluid activity.
Keywords: Monazite dating; K-Ar geochronology; Silesian Domain; thermal overprints; Bohemian Massif